2022
DOI: 10.3390/s22186911
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning-Based Feature Extraction of Acoustic Emission Signals for Monitoring Wear of Grinding Wheels

Abstract: Tool wear monitoring is a critical issue in advanced manufacturing systems. In the search for sensing devices that can provide information about the grinding process, Acoustic Emission (AE) appears to be a promising technology. The present paper presents a novel deep learning-based proposal for grinding wheel wear status monitoring using an AE sensor. The most relevant finding is the possibility of efficient feature extraction form frequency plots using CNNs. Feature extraction from FFT plots requires sound do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…By extracting features tailored to different industrial grinding conditions, they tested the recognition of grinding wheel wear states using t-SNE and PCA clustering algorithms. The study confirmed the outstanding efficiency of the pre-trained CNN in automatically extracting features from frequency maps [7]. Guo Bi et al employed long short-term memory (LSTM), a specialized type of Recurrent Neural Network (RNN), to construct a regression prediction model for wheel state, utilizing AE spectrums as the model input.…”
Section: Of 20mentioning
confidence: 72%
See 1 more Smart Citation
“…By extracting features tailored to different industrial grinding conditions, they tested the recognition of grinding wheel wear states using t-SNE and PCA clustering algorithms. The study confirmed the outstanding efficiency of the pre-trained CNN in automatically extracting features from frequency maps [7]. Guo Bi et al employed long short-term memory (LSTM), a specialized type of Recurrent Neural Network (RNN), to construct a regression prediction model for wheel state, utilizing AE spectrums as the model input.…”
Section: Of 20mentioning
confidence: 72%
“…The SNR OUT and MSE of the denoised signals using EMD, ICEEMDAN, and the method employed in this paper are shown in Table 1. Formulas (7) and ( 8) illustrate the calculation, where n represents the sample quantity, x i denotes the original signal, and xi represents the denoised signal. The SNR OUT obtained by our method was higher than that of EMD and ICEEMDAN denoising, while the MSE was lower than that of EMD and ICEEMDAN.…”
Section: Vmd Algorithm For Denoising Ae Signalsmentioning
confidence: 99%
“…Studies have shown that machine learning algorithms can effectively predict tool wear rates in various machining operations, such as milling [14], turning [15], and grinding [16]. Hybrid models combining ML algorithms with optimization techniques have also been proposed and shown to have high accuracy in predictions [17].…”
Section: Introductionmentioning
confidence: 99%
“…The application of acoustic emission technology is also difficult, and the recording of acoustic emission signals may be affected by the environment and contact area to produce noise [14]. For this reason, scholars have proposed a variety of noise reduction methods.…”
Section: Introductionmentioning
confidence: 99%